Pengaruh Sosialisasi Kesadaran Berkeselamatan di Jalan dalam Membangkitkan Sikap Safety Riding pada Generasi Z - Arbaningrum, Rizka (Civil Infrastructure Engineering and Architectural Design, 2023)
In fact, traffic accidents are a routine occurrence in the world and are one of the biggest causes of death in the world. Based on data obtained by WHO, traffic accidents cause 1.2 million deaths per year in low and middle income countries. 1000 deaths per day for under the age of 25 in the world so that traffic accidents are the highest cause of death for the category of children and adolescents in the age range of 5 to 29 years. However, one thing that is of concern is how to change the societal paradigm of traffic behavior so as to foster a culture of safety, especially from an early age. One of the strategic steps is through outreach to students from Kindergarten, Elementary, Middle School to SMA/SMK levels. The community service program is carried out at Pembangunan Jaya Middle School, located on Jl. Bintaro Utama 3A Pondok Karya Village, Pondok Aren sub-district, South Tangerang city. In socialization activities carried out at the initial stage and at the final stage by distributing pretest and posttest, of course this serves to find out the understanding of the material conveyed by the resource persons. Data processing from pretest and posttest results using IBM SPSS assistance by testing several testers. Of course, it is hoped that the results of the test will show understanding from the students of SMP Pembangunan Jaya so that later it can raise awareness about improving safety. Based on the results of the paired samples t test analysis using IBM SPSS in Figure 5, p = 0.00 (p <0.05), so that Ha is accepted and H0 is rejected, meaning that there is a significant influence on the socialization activities to raise awareness on road safety in Generation Z especially on the theme of Attitude towards Safety Riding.